Basics of engineering economy - Blank, Leland T.; Tarquin, Anthony J. (McGraw-Hill, 2014)
Covers the basic techniques and applications of engineering economy for all disciplines in the engineering profession. This book helps you explain and demonstrate the principles and techniques of engineering economic analysis as applied in different fields of engineering